Bifunctional oxygen reduction and evolution activity in brownmillerites Ca2Fe(1- x)CoxO5 - Thundiyil, S.; Kurungot, S.; Devi, R. N. (ACS Omega, 2019)
State-of-the-art catalysts for oxygen reduction and evolution reactions (ORR and OER), which form the basis of advanced fuel cell applications, are based on noble metals such as Pt and Ir. However, high cost and scarcity of noble metals have led to an increased demand of earth-abundant metal oxide catalysts, especially for bifunctional activity in ORR and OER. The fact that Pt and Ir or C, the cost-effective alternatives suggested, do not display satisfactory bifunctional activity has also helped in turning the interest to metal oxides which are stable under both ORR and OER conditions. Brownmillerite A2B2O5 type oxides are promising as bifunctional oxygen electrocatalysts because of intrinsic structural features, viz., oxygen vacancy and catalytic activity of the B-site transition metal. In this study, Co-doped Ca2Fe2O5 compounds are synthesized by the solid state method and structurally analyzed by Rietveld refinement of powder X-ray diffraction data. The compound Ca2Fe2O5, crystallizing in the Pcmn space group has alternative FeO4 tetrahedral and FeO6 octahedral layers. Its Co-doped analogue, Ca2Fe1.75Co0.25O5, also crystallizes in the same space group with both tetrahedral and octahedral Fe positions substituted with Co. However, Ca2FeCoO5 in the Pbcm space group shows interlayer ordering with Co-rich octahedra connected to Fe-rich tetrahedra and vice versa. Oxygen bifunctional activities of these catalysts are monitored by rotating disc electrode and rotating ring disc electrode techniques in alkaline media. A close analysis of the ORR and OER was conducted through comparison of various parameters such as onset potential, current density, halfwave potential, and other kinetic parameters, which suggests that the presence of Co in the B site aids in achieving better bifunctional activity and bulk conductivity. In addition, Co(II)/Co(III) redox systems and their comparative concentrations also play a decisive role in enhancing the activity.